Advancing Network Infrastructure: Integrating VXLAN Technology with Automated Circuit Operations and NOS Configurations - Efendi, Arfan; Husna, Diyanatul; Nugraha, I Gde Dharma (International Journal of Electrical, Computer, and Biomedical Engineering, 2023)
Enhancing network infrastructure is achieved through integrating VXLAN technology, Python-automated circuit operations, and Ansible-driven Network Operating System (NOS) configurations, complemented by GitHub for reliable configuration backups. VXLAN, a robust network virtualization protocol, addresses the challenges of managing extensive network segments. Python scripts facilitate the automated analysis, creation, and management of network circuits, significantly boosting efficiency and accuracy. Ansible, a powerful automation tool, is employed to streamline NOS configurations, ensuring consistency and reducing manual overhead in network settings. Concurrently, GitHub, working in tandem with crontab scheduling, offers a dependable platform for the automated, regular backup of configurations, thus enhancing network resilience and simplifying recovery processes. The collective implementation of VXLAN, Python, and Ansible automation, along with GitHub for configuration management, marks a notable advancement in operational efficiency, underscoring their importance as critical components in the modernization and security of network infrastructures.